The Solar-eclipse method of geodetic distance determination - Garcia, Benigno (1962)
The science of astronomy has been developed to such a high degree that, from data on the dimensions, relative distances, and relative motions of the sun, the moon, and the earth, it is possible to calculate the size and speed of the moon's shadow during a total solar eclipse; likewise, its path of totality and the precise time of passage over geographical localities. If, with the aid of modern photoelectric or sound-film techniques, the times of beginning and ending of totality are observed at two stations, the distance between them can be determined from the velocity-time relationship with the necessary corrections. By this method, the Finnish Geodetic Institute obtained the distance from Brazil to the Gold Coast with an uncertainty of ± 94 meters, after successful observations on the total solar eclipse of May 20, 1947 with a specially designed camera.
Thesis (B.S. Geodetic Engineering)--University of the Philippines, Diliman.
Keywords: Solar eclipses; Geodesy